Dos especies nuevas de calathea (Marantaceae) de la Amozonia Colombiana - Suárez Stella; Galeano Gloria (Caldasia)
Two new species of Marantaceae from Amazonian Colombia are described and illustrated: Calathea caquetensis and C. compacta. C. caquetensis is apparently related to C. attenuata and C. silvosa. C. compacta seems to be related to C. ecuminata, C. pearcei and C. schunkei. Se describen e ilustran dos especies nuevas de Marantaceae de la Amazonia colombiana: Calathea caquetensís y C. compacta. C. caquetensis está aparentemente relacionada con C. attenuata y C. silvosa. C compacta parece estar relacionada con C. acuminata, C. pearcei y C. schunkei.